Degradation of atrazine by electrochemically activated persulfate using BDD anode: Role of radicals and influencing factors. (March 2018) - Bu, Lingjun; Zhu, Shumin; Zhou, Shiqing
Abstract: A novel advanced oxidation process using boron-doped diamond (BDD) anode to activate persulfate (PS) with low concentration of electrolyte was systematically investigated in this study. Compared to direct electrochemical oxidation of atrazine (ATZ) using BDD anode, the addition and activation of PS significantly declined the demand for electrolytes. It was confirmed by scavenger experiments that both radical and non-radical oxidation occurred in this system. Degradation of ATZ was enhanced with the increase of current density and dosage of PS, and decrease of initial pH. However, the increase of current density can also lead to the decrease of current efficiency, then increase of energy consumption. Besides, the inhibitory effect of anions on the degradation of ATZ followed the order of HCO 3 − > H 2 PO 4 − > NO 3 −, while the presence of Cl − accelerated the degradation of ATZ. Furthermore, the degradation products mainly resulting from de-alkylation, de-chlorination, and hydroxylation were detected. Due to the distinctive preference to ethyl group in BDD/PS system, the formation of deethyl-atrazine was quicker than that of deisopropyl-atrazine. The study aims to provide a comprehensive understanding on the potential application of BDD/PS system in water treatment. Graphical abstract: Highlights: Demand for electrolyte decreased significantly in BDD/PS system. Both radical and non-radical oxidation occurred in BDD/PS system. Dealkylation and dechlorination are two main reactions in degradation of ATZ.